(untitled) (Global Journal of Human-Social Science, 2023)
This paper seeks to question the relationship between lyrical subject and living subject as from the poem O rel gio e o sonho by Moacyr F lix originally published in the book O p o e o vinho 1959 work in which the poet said he had found his own face Highlighting the theme of memory we refer to Baudelaire s metaphor of the fencer and the relationship between Erfahrung and Erlebnis as well as between lived experience and poetic experience in Benjamin to support the hypothesis that affirmative of poetic identity in Felix s lyric is at the same time the realization of its loss